Nursing care process and help relationship in paediatric nursing - Ángeles Ferrer Pardavíla; Rosario García Sampedro; José María Barreiro Bello (Universidad de Alicante, 2012)
INTRODUCTION. The needed knowledge for nursing care must approach the person from biological, psychological, spiritual and social perspectives, spheres, points of view, framed in a conceptual model that organizes all the collected information, determines philosophy and establishes action lines within the context of the nursing attention process as an scientific method that systematizes work and takes the chosen model to practice. It is necessary to maintain interpersonal relationships in addition to ethical and legal knowledge and therapeutic communication with patients and relatives. We consider that all of these are key elements for the implementation of help relationship. OBJECTIVES. To reflect on care and help relationship in a nursing scope. To establish the existing links between nursing process and help relationship, focusing on a real case. To highlight, based on the results, the importance of its integration in care. OBSERVACIÓN CLÍNICA. DEVELOPMENT OF NURSING PROCESS AND HELP RELATIONSHIP. This study was made in the infant unit of Teresa Herrera Hospital (CH J. Canalejo. A Coruña). Description of an eleven months female infant case hospitalised with her mother. The infant carne in because a ponderal stagnation, connate cardiopathy (Aorta coartation, Arterial Ductus, Interventricular communication) and Down Syndrome. Needs assessment according to the Virginia Henderson's model, defining the nursing diagnosis with the NANDA taxonomy adapted to the informatic application for nursing care management (GACELA,). The diagnostics identified were: Mobility affectation, Alteration of body temperature, Risk of traumatism, Risk of low feeding intake, Parental function alteration, Mother anxiety, Risk of stress in the development of caregiving role, Risk of sleep impairment. With activities of: communication, feelings expression, anxiety coping, psychological support and positive reinforcement, a strong interpersonal communication and a significative relationship between the baby, her mother and the staff was established. The mother lived a positive and constructive change in her way of thinking and behaviour improving her problem resolution efficacy. CONCLUSIONS AND DISCUSSION. A conceptual model based on the Nursing Process can't be developed without focusing on help relationship (fundamental axis on care process) with patients and relatives. Nursing professionals need the adequated education to assume this kind of interventions, as well as more implication and responsibility in these interventions. We will highlight the importance of the work of multidisciplinary teams. We relyon for help relationship as a personal growth process of health system users and professionals, family implication being essential in this process.